The assessment of quality of life in children with tracheostomies and their families in a low to middle income country (LMIC). (November 2020) - Din, Taseer F; McGuire, Jessica; Booth, Jane; Lytwynchuk, Andrew; Fagan, Johannes J; Peer, Shazia
Abstract: Introduction: The Breatheasy© Tracheostomy Program based at the Red Cross War Memorial Children's Hospital, Cape Town, manages children mostly from poor socio-economic backgrounds. In our resource-limited setting, it is unclear how these families cope with the demands of a tracheostomised child. We aim to assess the quality of life (QOL) of tracheostomised children and their families as the first study of its kind in a low-resource setting. Methods: A descriptive, observational study was done to assess the QOL of tracheostomised children managed by the Breatheasy© Program over 10 months. Children with tracheostomies for longer than 6 months, complex syndromic children, and home ventilated children were included. The validated Paediatric Tracheotomy Health Status Instrument (PTHSI) was utilised, where a higher score implied a better outcome. Results: A total of 68 families were recruited. In 57 (85.1%) of the carers, the highest level of education achieved was primary or high school. Twenty-seven (42%) families reported having an annual household income of less than $675 US Dollars (<ZAR10, 000). Sixteen (24%) resided within informal housing. The mean scores for the 4 PTHSI domains were: physical symptoms 24.8/35 (70.9%), frequency/financial impact of medical visits 14.2/15 (94.7%), QOL of child 8.8/15 (58.7%), QOL of carer 62.3/85 (73.3%); the overall score was 110.2/150 (73.5%). There was no significant correlation between total PTHSI and annual household income, carer's educational status or type of housing. Children with a concomitant major medical condition had a significantly poorer total PTHSI scores (p-value 0.024). Conclusion: Tracheostomy care compounds challenging socio-economic circumstances. In our experience, with adequate training, home-care nursing is not necessary. Despite difficult living conditions, the Breatheasy© Program empowers children and their families to live independently of the hospital system and appear to be thriving. The decision to perform a paediatric tracheostomy should not be influenced by the carer's education level, socio-economic status, or on the basis of formal or informal housing. Children with major medical comorbidities represent a group that requires more support.